Novel quinazolin-4-one derivatives as potentiating agents of doxorubicin cytotoxicity - Pospisilova, Monika; Andrs, Martin; Seifrtova, Martina; Havelek, Radim; Jun, Daniel; Tomsik, Pavel; Prchal, Lukas; Dolezal, Rafael; Tichy, Ales; Kucera, Tomas; Korabecny, Jan; Rezacova, Martina (Bioorganic chemistry, 2019)
We report the design, synthesis and biological evaluation of 17 novel 8-aryl-2-morpholino-3,4-dihydroquinazoline derivatives based on the standard model of DNA-PK and PI3K inhibitors. Novel compounds are sub-divided into two series where the second series of five derivatives was designed to have a better solubility profile over the first one. A combination of in vitro and in silico techniques suggested a plausible synergistic effect with doxorubicin of the most potent compound 14d on cell proliferation via DNA-PK and poly(ADP-ribose) polymerase-1 (PARP-1) inhibition, while alone having a negligible effect on cell proliferation.
Keywords: Cancer; Chemosensitization; Morpholines; morfoliny; poly(ADP-ribosa)polymerasa 1; Quinazolinones; NU7441; Humans; Phosphatidylinositol 3-kinase; Poly(ADP-ribose) polymerase-1; chinazolinony; buňky HT-29; proteinkinasa aktivovaná DNA; doxorubicin; Female; Drug Synergism; Antineoplastic Agents; Doxorubicin; HT29 Cells; jaderné proteiny; lidé; zvířata; proliferace buněk; myši; DNA-Activated Protein Kinase; outbrední kmeny zvířat; synergismus léků; apoptóza; Drug Design; Mice; Animals, Outbred Strains; ženské pohlaví; Cell Proliferation; Nuclear Proteins; racionální návrh léčiv; DNA-dependent protein kinase; protinádorové látky; inhibitory enzymů; Animals; Poly (ADP-Ribose) Polymerase-1; Enzyme Inhibitors; Apoptosis